Characterizing the Compressive Piezoresistive Behavior of Smart Cement Using Vipulanandan Model - Vipulanandan, C. (University of Jaffna, 2022)
The effect of water-to-cement ratio (w/c) on the piezoresistive behavior of smart cement was investigated. The sensing property of the smart cement was modified with 0.1% carbon fiber (CF) and the behavior was investigated up to 28 days of curing. Electrical resistivity was identified as the sensing and monitoring property for the smart cement. The initial resistivity (ρo) of the smart cement decreased from 1.03 Ω-m to 1 Ω-m and 0.9 Ω-m, a 3% and 12% reduction when the w/c ratio was increased from 0.38 to 0.44 and 0.54 respectively, higher than the changes in the initial unit weights of the cement slurry. For the smart cement the electrical resistivity increased with the applied compressive stress (New Technology). The piezoresistive axial strain of the smart cement at failure with water-cement ratio of 0.38 and curing of 28 days was over 300% compared to the failure strain cement of 0.2%, 1500 times (150,000%) higher make it a highly sensing material. The Vipulanandan p-q piezoresistive model predicated the piezoresistive compressive stress – change in resistivity relationship of the smart cement very well. Linear correlations were observed between resistivity index (RI24hr) and compressive strength of smart cement for different curing times.
Keywords: Water-to-cement ratio; Electrical resistivity; Piezoresistivity; Modeling